2015
DOI: 10.17265/1934-7391/2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Morphological Characterization by Using Transmission Electron Microscopy

Abstract: Bacteriophages or more commonly "phages" are bacterial viruses. They are ubiquitous and good indicators of bacterial contaminations since their prevalence is high in those environments where their hosts are abundant. Phage classification is based on morphology and for this reason, even though it is considered an old technique, TEM (Transmission Electron Microscopy) still plays a key role in their characterization. In the present work, the authors focused on TEM analysis of phage ɸApr-1 isolated against Lactoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…SEM analysis is a rapid and simple method of characterizing phages, aiding in the identification of novel phages and attribution to families [ 36 ]. SEM observation indicated that 4 out of 17 phages, isolated from different samples, belonged to the order Caudovirales , with 2 of the isolates being part of the Myoviridae family.…”
Section: Discussionmentioning
confidence: 99%
“…SEM analysis is a rapid and simple method of characterizing phages, aiding in the identification of novel phages and attribution to families [ 36 ]. SEM observation indicated that 4 out of 17 phages, isolated from different samples, belonged to the order Caudovirales , with 2 of the isolates being part of the Myoviridae family.…”
Section: Discussionmentioning
confidence: 99%
“…No LMPs were isolated from manure or silage samples from farm I, which may be attributed to a high level of hygiene and the frequent removal of manure. Bacteriophages are common and reliable indicators of bacterial contamination because their occurrence is high in surroundings where their hosts are numerous [ 28 ]. The high occurrence of LMPs in silage samples shows that inadequately fermented silage, as well as dairy farm environments in general, are suitable substrates for LMP isolation.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of isolated phages was based on the morphology observed under TEM, which plays a key role in phage characterization [ 28 , 30 ]. The classification was based on the characteristics of the head and the tail of the phage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM analysis is a rapid and simple method of characterizing phages, aiding in the identification of novel phages and attribution to families [12]. SEM observation indicated that 4 out of 17 phages, isolated from different samples, belonged to the order Caudovirales, with 2 of the isolates being part of the Myoviridae family.…”
mentioning
confidence: 99%